2008
DOI: 10.1021/bi800816v
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and Distal-Heme Pocket Mutations Exhibit Additive Effects on the Structure and Function of Hemoglobin

Abstract: Protein engineering strategies seek to develop a hemoglobin-based oxygen carrier with optimized functional properties, including (i) an appropriate O 2 affinity, (ii) high cooperativity, (iii) limited NO reactivity, and (iv) a diminished rate of autooxidation. The mutations αL29F, αL29W, αV96W and βN108K individually impart some of these traits and in combinations produce hemoglobin molecules with interesting ligand-binding and allosteric properties. Studies of the ligand-binding properties and solution struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 64 publications
2
20
0
2
Order By: Relevance
“…Similar experiments were carried out with hybrid tetramers at 10% photolysis. In the case of hybrid tetramers, the observed time courses were fitted to two exponential expressions, one for the wild-type subunit and one for the mutant subunit (34,37). Although physiologically more relevant, the assignment of the phases to ␣ and ␤ subunits within Hb tetramers can be ambiguous, whereas the assignment of rate parameters is straightforward for isolated ␣ and ␤ chains.…”
Section: Resultsmentioning
confidence: 99%
“…Similar experiments were carried out with hybrid tetramers at 10% photolysis. In the case of hybrid tetramers, the observed time courses were fitted to two exponential expressions, one for the wild-type subunit and one for the mutant subunit (34,37). Although physiologically more relevant, the assignment of the phases to ␣ and ␤ subunits within Hb tetramers can be ambiguous, whereas the assignment of rate parameters is straightforward for isolated ␣ and ␤ chains.…”
Section: Resultsmentioning
confidence: 99%
“…For example, active site mutations that alter the polarity or hydrophobicity of the distal heme pocket can produce direct changes in the association constant for O 2 binding, but such mutations typically compromise structural stability or increase the susceptibility to heme autoxidation (the spontaneous oxidation of the heme iron from the ferrous Fe 2+ state to the ferric Fe 3+ state, which renders Hb functionally inert as an O 2 -transport molecule) (29). In contrast, mutations remote from the active site-like those at β13 and β83-can potentially produce fine-tuned changes in O 2 -affinity with minimal pleiotropic effects through subtle displacements of the allosteric equilibrium (28)(29)(30). Within the set of all possible mutations that produce functionally equivalent effects on Hb-O 2 affinity, those that incur a lesser magnitude of deleterious pleiotropy are predicted to have a higher fixation probability, and such mutations may therefore contribute disproportionately to biochemical adaptation (31)(32)(33).…”
Section: Mechanisms Of Hb Adaptation and Causes Of Parallelism At Thementioning
confidence: 99%
“…The optimum parameters for oxygen transport by Hb in human red blood cells appear to be a P 50 = 30-50 lM (20-40 mm Hg) at 37°C and association (k¢ O2 ) and dissociation (k O2 ) rate constants ‡ 1 lM (22,35,63,76,93,104,150). The mechanisms that govern O 2 binding have been established in detail and used to design recombinant Hb molecules with P 50 values that range from £ 0.2 to ‡ 200 lM, using both allosteric and active site mutations (14,35,83). The more difficult challenge has been to inhibit the rate of NO scavenging without markedly altering the rates of O 2 uptake and release.…”
Section: Controlling O 2 Affinity and Nodmentioning
confidence: 99%
“…Recent work has demonstrated that, in addition to NOD activity, spontaneous and H 2 O 2 -induced oxidation of Hb iron atoms to the ferric and ferryl states can lead to diverse pathophysiologies that are thought to be related to hemin loss and destruction, iron-catalyzed redox reactions, and globin (83) and NOD rates (99) and for reducing the blood pressure effect in rat model systems by lowering k¢ NOD (36,99). rHb1.1 contains the Hb Presbyterian mutation bN108K to maintain a high P 50 .…”
Section: Autooxidation Hemin Loss and Reactivity With H 2 Omentioning
confidence: 99%